Men's laws, women's lives : a constitutional perspective on religion, common law, and culture in South Asia - Jaising, Indira (New Delhi : Women Unlimited, 2005)
Contributed articles.
Includes bibliographical references.
Keywords: Women -- South Asia -- Congresses